Determinan Permintaan Pariwisata di ASEAN (Analisis Data Panel Dinamis 2000-2015) [Tourism Demand Determinants in ASEAN (Dynamic Panel Data Analysis 2000-2015)] - Christina Ruth Elisabeth (DeReMa (Development Research of Management): Jurnal Manajemen, 2018)
The purpose of this study is to examine the determinants of tourism demands in ASEAN during the period of 2000-2015. This study uses Generalized Method of Moments (GMM) to measure the impact of tourism price, infrastructure, health, openness, government spending on education, risk of tourism and word of mouth effect to the number of tourist arrivals in ASEAN. The result shows that the significant determinants are physical investment, health, openness, risk of tourism and word of mouth effect. Meanwhile, tourism price and government expenditure on education do not significantly affect the number of tourist arrivals. This study recommends the need for ASEAN member countries to enhance cooperation in developing infrastructure, training on safety and health, trade negotiations and tourism promotion.Bahasa Indonesia Abstrak: Tujuan penelitian ini adalah untuk mengetahui deteminan dari permintaan turis masuk di ASEAN, sepanjang periode 2000-2015. Studi ini menggunakan model Generalized Method of Moments (GMM) untuk mengukur dampak dari harga pariwisata, infrastruktur, tingkat kesehatan, keterbukaan, pengeluaran pemerintah untuk pendidikan, resiko pariwisata dan efek word of mouth terhadap jumlah turis masuk ke ASEAN. Hasil penelitian menunjukkan bahwa faktor yang signifikan mempengaruhi adalah investasi infrastruktur, tingkat kesehatan, keterbukaan, resiko pariwisata dan efek word of mouth. Sementara, harga pariwisata dan pengeluaran pemerintah untuk pendidikan tidak signifikan mempengaruhi jumlah turis masuk. Studi ini merekomendasikan pentingnya negara ASEAN untuk meningkatkan kerjasama dalam pengembangan infrastruktur, training keamanan dan kesehatan, meningkatkan negosiasi perdagangan dan promosi pariwisata.